PERMASALAHAN DAN KENDALA PENYELESAIAN SENGKETA KONSUMEN MELALUI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) - Kurniawan Kurniawan (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Consumer dispute can be resolved through on courts or outside the court based on voluntary choice of the parties. Settlement of dispute through the court provisions on the article 45. Dispute of the settlement can be solved out the court by using Consumer Dispute Settlement Body (BPSK).The purpose of establshing BPSK is to protec consumer and producer by designing consumer protection system that contain legal certainty and transparency the information. The existence of BPSK expected equality of justice especially to consumer that aggrieved by consumer. It because the dispute between consumer and producer generally involved in small value so that the consumer hesitate to registered his case to judicial process. There is no adequate between the court fee and indemnification perceived. The problems that the decision of BPSK has characteristic final and binding however it can be carried out to the district court and the decision cannot be executed directly or realized. Keywords: consumers right, consumer’s protection, dispute resolution.